Transformations in the models of journalists formation in Spain - Pestano Rodríguez, Juan Manuel; Rodríguez Wangüemert, Carmen; del Ponti, Patricia (Estudios sobre el Mensaje Periodístico, 2012)
We study the evolution of journalism training models found in Spain during the twentieth century, in wich we find four different models. These models have reached full development at certain time points and three of them have evolved until now. We emphasize how the specific higher education model is now immersed in a transformation process due to the changes that the European convergence implies; we analyze diverse elements of this transformation and we expose some strengths and weaknesses of this model, in the face of other training models which coexist with the institutional.